151. Hyperthermia, generated by focused ultrasound, in combination with radiations for a more effective glioblastoma therapy. (December 2018) - Borasi, G.
Abstract : Purpose: The existing transcranial focused ultrasound device (Insightec Exablate 4000 Neuro) can induce hyperthermia in a brain region ten times larger than was recently covered with ablation[1] . The purpose of this work was to theoretically derive how a relatively small volume of glioblastoma multiforme (GBM) can be effectively treated by combining focused ultrasound based hyperthermia with an external beam radiotherapy. Methods: We applied a mathematical descriptions of GBM proliferation and diffusion, in the frame of the reaction diffusion theory. We formulated equations capturing of the impact of radiotherapy and heat on GBM in the reaction diffusion equation, including the regrowth induced by stem cells[2] . Results: Our calculated results show that the expected patient survival could be significantly improved by this treatment[3] . For the future, due to the lower power required for a single heating point, a somewhat lower frequency could be hypothesized, without risks of cavitation. This modification would allow the heating of larger tumors in less central regions. Conclusions: The proposed methodology, now limited to a small tumors in a quite central location, can be easily improved in several different respects. These results advocate thorough experiments to validate this very promising theoretical therapeutic benefit.